Customers' satisfaction towards workmanship and quality performance of low cost housing in Sarawak / Noraziah Wahi … [et al.] - Wahi, Noraziah; Ismail, Noor Akmal Adillah; Mohamed Nordin, Rafizah (2012)
The concept of customer satisfaction is very popular nowadays in any industries including housing industry. In order to enhance quality in the housing industry especially in low cost housing, the government has introduced some standardisations such as MS1064 and CIS1&2. However, these standardizations are not implemented thoroughly in low cost housing sector, for the reasons of lower cost budget for low cost housing. The objective of the survey is to determine customer satisfaction towards workmanship and quality performance of low cost houses in Sarawak. The data required will be gathered by two methods which are literature review and questionnaire survey. Statistical Package for Social Sciences Software (SPSS) will be used for data analysis based on frequency and factor analysis. The satisfaction level of customers of low cost house in Sarawak is expected from the survey.